Condutas para reparação da cavidade anoftálmica no Brasil - Fernandes de Sousa, Roberta Lilian [UNESP]; Schellini, Silvana Artioli [UNESP]; Moreira Zornoff, Denise de Cassia [UNESP]; Padovani, Carlos Roberto [UNESP] (Conselho Brasileiro de Oftalmologia, 2012)
Purpose: To determine the most common approach to repair the anophthalmic socket in Brazil, and to compare the data with the trends in other countries.Methods: Exploratory study using electronic questionnaire sent by Internet to ophthalmologists members of the Brazilian Orbit and Oculoplastic Society (SBCPO). The received answers were analyzed by adhesion analysis, using Chi-square test.Results: We received 75 answered questionnaires. Fifty-three per cent of the respondents frequently treat anophthalmic socket and use the 18 mm diameter polymethylmethacrylate sphere in the majority of the surgeries, mainly covered by sclera (92%). Only seven interviewees had used integrated implants with pegging procedure. Eighty-two per cent of the ophthalmologists use the dermolipid graft to reconstruct the anophthalmic socket. They also follow the patients bi annually.Conclusions: The treatment of anophthalmic socket in Brazil generally involve polymethylmethacrylate sphere with 18 mm diameter. Pegging procedure is uncommon between us.
Trends on anophthalmic socket repair in Brazil
Keywords: Anophthalmos; Eye artificial; Orbit; Eye evisceration; Brazil